Optimization Of Production Employee Shift Scheduling Using The Simple Additive Weighting Method At PT Japfa Comfeed Gedangan: Optimasi Penjadwalan Shift Karyawan Produksi Dengan Metode Simple Additive Weighting Di Pt Japfa Comfeed Gedangan - Rahandi Ramadhan; Rr. Rochmoeljati (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
This technical implementation study discusses the optimization of production employee shift scheduling at PT Japfa Comfeed Indonesia Tbk using the Simple Additive Weighting (SAW) and Integer Linear Programming (ILP) methods. The scheduling model applied considers performance factors, job satisfaction, work discipline, and work knowledge to form teams with balanced total values, thereby increasing work effectiveness and efficiency. The rule-based scheduling method shows more regular and consistent shift distribution results, with a